THE INFLUENCE OF LEADERSHIP, WORK DISCIPLINE AND WORK ENVIRONMENT ON THE JOB SATISFACTION OF PROTOCOL EMPLOYEES AT THE ADPIM BUREAU OF THE REGIONAL SECRETARY CENTRAL SULAWESI PROVINCE - Deby, Reni Siska; Kornelius, Yoberth; Adda, Harnida Wahyuni (JURNAL INTERNASIONAL UNIVERSITAS TADULAKO, 2025)
The objectives of this study are as follows: (1) To determine and analyse the effect of leadership, work discipline and work environment simultaneously on employee job satisfaction in the Public Relations and Protocol Section of the Regional Secretary of Central Sulawesi Province; (2) To determine and analyse the effect of leadership partially on employee job satisfaction in the Public Relations and Protocol Section of the Regional Secretary of Central Sulawesi Province; (3) To determine and analyse the effect of work discipline partially on employee job satisfaction in the Public Relations and Protocol Section of the Regional Secretary of Central Sulawesi Province; and (4) To determine and analyse the effect of work environment partially on employee job satisfaction in the Public Relations and Protocol Section of the Regional Secretary of Central Sulawesi Province. This research uses the type of causal associative research with a sample of 30 respondents who are employees in the Public Relations and Protocol Section of the Adpim Bureau of the Regional Secretary of Central Sulawesi Province. Data collection techniques using questionnaires, observation and documentation and data analysis techniques using Multiple Regression Analysis. The results showed that: (1) Leadership, work discipline and work environment simultaneously have a positive and significant effect on employee job satisfaction in the Public Relations and Protocol Section at the Adpim Bureau of the Regional Secretary of Central Sulawesi Province with an F-count value of 20.942 or Sig-F = 0.000 < α 0.05; (2) Leadership partially has a positive and significant effect on employee job satisfaction of the Public Relations and Protocol Section at the Adpim Bureau of the Regional Secretary of Central Sulawesi Province, with a t-count value (6,508) or Sig-t value (X1) = 0.000 < α 0.05 (3) Work discipline partially has a positive and significant effect on employee job satisfaction of the Public Relations and Protocol Section at the Adpim Bureau of the Regional Secretary of Central Sulawesi Province, t-count value (2,225) or Sig-t (X2) = 0.035 < α 0.05; (4) The work environment partially has a positive and significant effect on job satisfaction of employees of the Public Relations and Protocol Section at the Adpim Bureau of the Regional Secretary of Central Sulawesi Province, t-count value (2.809) or Sig-t value (X3) = 0.009 < α 0.05.Tujuan penelitian ini adalah sebagai berikut: (1) Untuk mengetahui dan menganalisis pengaruh kepemimpinan, disiplin kerja dan lingkungan kerja secara serempak terhadap kepuasan kerja pegawai pada Bagian Humas dan Protokol Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah; (2) Untuk mengetahui dan menganalisis pengaruh kepemimpinan secara parsial terhadap kepuasan kerja pegawai pada Bagian Humas dan Protokol Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah; (3) Untuk mengetahui dan menganalisis pengaruh disiplin kerja secara parsial terhadap kepuasan kerja pegawai pada Bagian Humas dan Protokol Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah; dan (4) Untuk mengetahui dan menganalisis pengaruh lingkungan kerja secara parsial terhadap kepuasan kerja pegawai pada Bagian Hunas dan Protokol Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah. Penelitian ini menggunakan jenis penelitian asosiatif kausal dengan sampel sebanyak 30 responden yang merupakan pegawai pada Bagian Humas dan Protokoler Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah.Teknik pengumpulan data menggunakan kuesioner, observasi dan dokumentasi serta teknik analisis data menggunakan Analisis Regresi Linier Berganda (Multiple Regression). Hasil penelitan menunjukan bahwa: (1) Kepemimpinan, disiplin kerja dan lingkungan kerja secara serempak berpengaruh positif dan signifikan terhadap kepuasan kerja pegawai Bagian Humas dan protokoler pada Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah dengan nilai nilai F-hitung sebesar 20,942 atau Sig-F = 0,000 < α 0,05; (2) Kepemimpinan secara parsial berpengaruh positif dan signifikan terhadap kepuasan kerja pegawai Bagian Humas dan protokoler pada Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah, dengan nilai t-hitung (6,508) atau nilai Sig-t (X1) = 0,000 < α 0,05 (3) Disiplin kerja secara parsial berpengaruh positif dan signifikan terhadap kepuasan kerja pegawai Bagian Humas dan protokoler pada Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah, nilai t-hitung (2,225) atau Sig-t (X2) = 0,035 < α 0,05; dan (4) Lingkungan kerja secara parsial berpengaruh positif dan signifikan terhadap kepuasan kerja pegawai Bagian Humas dan protokoler pada Biro Adpim Sekretaris Daerah Provinsi Sulawesi Tengah, nilai t-hitung (2,809) atau nilai Sig-t (X3) = 0,009 < α 0,05.